Perceived differences between natural and convolution reverberation types in 5.0 surround sound - Shriram, Alluri R. (2011)
This Graduate Thesis investigates the perceived differences between natural and convolution reverberation in surround sound. Two spaces with distinct reverberation times were used for this study. Initially three musical excerpts from three instruments (Cello, Oboe, and Piano) were recorded in a dry studio environment. Then the Impulse Response (IR) of the spaces was captured using two methods: balloon burst and sine sweep. The dry excerpts were then recorded in the spaces to capture the natural reverberation pattern while the IRs were convolved with them to create the artificial reverberation excerpts. A listening test was then conducted using six perceptual scales to rate these 18 excerpts (3 reverberation types, 3 instruments and 2 spaces). The main findings were that the “artificiality” in the artificial excerpts could be perceived by the listeners. The sine sweep reverberation type was perceived to be more similar to the natural reverberation of the space rather than the balloon burst method. The two artificial reverberation types were better suited to a longer reverberation time and a larger space while being best suited for the Oboe and least suited for the Piano. Though a few interesting insights into the perception of convolution reverberation have been provided, the main success of this thesis is the creation of a methodology that can be used for future perceptual studies in artificial reverberation which aim to investigate and improve its perception.